PENGEMBAGAN MEDIA PEMBELAJARAN LEMARI KATA BERBASIS 3D TERHADAP KETERAMPILAN MEMBACA DIKELAS II SEKOLAH DASAR - Ade Ainun Nadilah; Rina Yuliana; Encep Andriana (JURNAL HANDAYANI PGSD FIP UNIMED, 2023)
The goal of this study is to create word cabinet learning media for grade II SD reading skills based on 3D technology and to create word cabinet learning media that match the requirements for being practical to use in Indonesian language courses for grade II SD reading abilities. The problem analysis, data collecting, product design, design validation, design revision, and product testing constitute the research methodology that Sugiyono modified. Expert validation tests are performed by media experts, material experts, and language experts on this educational media. A product trial was conducted with the research subject, class II pupils at Panunggulan 3 Elementary School, after a validation test by a team of experts. The outcomes of the of student responses obtained an average score of 83% in the "very good" category. Based on the results of the study it can be concluded that vocabulary learning media for 3D-based reading skills for second grade elementary school students is "very feasible" for use in learning Indonesian in reading skills in second grade elementary school.Keyword: Learning Media, Word Cabinets, Reading Skills Tujuan dari penelitian ini adalah untuk membuat media pembelajaran lemari kata untuk keterampilan membaca kelas II SD berbasis teknologi 3D dan untuk membuat media pembelajaran lemari kata yang sesuai dengan syarat praktis untuk digunakan pada mata pelajaran bahasa Indonesia kemampuan membaca kelas II SD. Analisis masalah, pengumpulan data, desain produk, validasi desain, revisi desain, dan uji coba produk merupakan metodologi penelitian yang dimodifikasi oleh Sugiyono. Uji validasi ahli dilakukan oleh ahli media, ahli materi, dan ahli bahasa pada media pendidikan ini. Uji coba produk dilakukan dengan subjek penelitian siswa kelas II SD Negeri 3 Panunggulan, setelah dilakukan uji validasi oleh tim ahli. Hasil darirespon siswa memperoleh nilai rata-rata sebesar 83% dengan kategori “sangat baik”. Berdasarkan hasil penelitian dapat disimpulkan bahwa media pembelajaran lemari kata pada keterampilan membaca berbasis 3D pada peserta didik kelas II SD “sangat layak” untuk digunakan dalam pembelajaran Bahasa Indonesia dalam keterampilan membaca di kelas II SD.Kata Kunci: Media Pembelajaran, Lemari Kata, Keterampilan Membaca